2006
DOI: 10.1080/01411920500402052
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, competence and reflection in the rhetoric of professional development

Abstract: This article explores the rhetorical work done by discourses of professional development in education. In particular it outlines the ways in which the rhetoric of technical expertise, competence and reflective practice are deployed to mobilise professional practices and identities in particular ways and position certain practices and dispositions as specifically professional. The article explores the ways in which audiences are mobilised and the strategies to persuade educators that particular discourses of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 20 publications
(15 reference statements)
0
59
0
2
Order By: Relevance
“…However, in addition to simple design efficacy (given we wish to identity effective practice), our intention is to utilise the symbolic power of RCTs to support research impact. In other words, we see the potential of RCT design as a rhetorical tool (Edwards & Nicholl, 2006). We are not so naive as to think that even the application of modes of evidence-gathering which symbolise 'hard science' necessarily precipitate evidence-informed policy making.…”
Section: IXmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to simple design efficacy (given we wish to identity effective practice), our intention is to utilise the symbolic power of RCTs to support research impact. In other words, we see the potential of RCT design as a rhetorical tool (Edwards & Nicholl, 2006). We are not so naive as to think that even the application of modes of evidence-gathering which symbolise 'hard science' necessarily precipitate evidence-informed policy making.…”
Section: IXmentioning
confidence: 99%
“…We approach this question drawing on a Foucaultian 'analysis of discourse' approach (Parker, 1990;Parker & Burman, 1993), interwoven with recognition as to how discourses may be articulated and wielded by policymakers, journalists and other individuals as policy rhetorics (Edwards and Nicholl, 2006;Edwards et al 2004;Francis, 2015) iv . From a Foucaultian perspective, discourses are not 'right or wrong', but produce 'regimes of truth' which elevate and naturalise particular productions of the world.…”
Section: Theoretical Lens and Analytic Approachmentioning
confidence: 99%
“…As well, the resulting decisions about the appropriate types and levels of support and who will provide that support will pre-determine the type of professional development that is made available and in what form it will be provided, without adequately addressing the needs of support practitioners such as teacher aides, for planning and reviewing 13 processes with other members of the students' support networks, and job-embedded learning experiences (Ghere & York-Barr, 2007;Groom, 2006). Research has shown that not including teachers and teacher aides in decisions about how practices will be reformed to be more inclusive leads to feelings of imposition and resentment on the part of practitioners, and therefore negative attitudes towards professional development designed to inform these changes Edwards & Nicoll, 2006;Forlin, 2006;Ghere & York-Barr, 2007;Howard & Ford, 2007;Timmons, 2006). …”
mentioning
confidence: 99%
“…Recently in the UK, the nature, structure, processes and effectiveness of Continuing Professional Development (CPD) have attracted a substantial amount of research and analysis, as well as on-going debates with regard to its nature and impact on pedagogic practices (e.g., Bolam, 2000;Edwards and Nicoll, 2006). Much of the current debate regarding CPD has been concerned with 'who and what is being developed, by whom and, most importantly, in whose interests' (Noffke, 1997, p. 334).…”
Section: Introductionmentioning
confidence: 99%
“…For example, teachers' thinking and attitudes should be considered in the context of a policy of widening participation, and the changing nature of teaching within globalising practices that require them to translate educational discourses and governmental initiatives into practice (Edwards and Nicoll, 2006). Current debates about the nature of professionalism and professional development have focused on three notions of professional practice, namely the technical expert, the competent practitioner and the reflective practitioner (Edwards and Nicoll, 2006). Increasingly, educators are positioned as being competent and reflexive in locating and translating educational initiatives into classroom practice.…”
Section: Introductionmentioning
confidence: 99%